Disinflating from moderate inflation in Latin America and the Caribbean (2007)
This paper studies the behavior of several macroeconomic variables during disinflationary episodes in Latin-America and the Caribbean (LAC). In particular, it focuses on disinflations from low and moderate peaks for the period 1973-2001. The methodology used for studying the average behavior of macroeconomic variables across disinflations overcomes the traditional problem of scarce long time series (of high frequency data) that has hindered the empirical research of monetary shocks in many LAC countries. Some of the important findings are as follows: (i) while GDP growth slowed down during the disinflations of the 70s and 80s, there is no evidence of this for the 90s; (ii) the trade balance significantly deteriorated during the disinflations; (iii) the nominal devaluation rate slowed down during the episodes; and (iv) the real exchange rate appreciated during the episodes.